2007
DOI: 10.1258/000456307779595931
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum dipeptidyl peptidase IV activity in patients with chronic tonsillitis

Abstract: An increased serum DPP IV activity was observed in TH patients compared with both RT patients and controls before tonsillectomy. After tonsillectomy, all activities were similar. The results suggest that serum DPP IV activity may have potential as a diagnostic marker for patients with TH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
2
1
0
1
Order By: Relevance
“…The pattern of activity shown by these enzymes differed depending on patient age and gender as well as their medical condition. This selective pattern has also been described in previous studies [1,3,7] and demonstrates that the changes observed are not the result of nonspecific cell proteolysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The pattern of activity shown by these enzymes differed depending on patient age and gender as well as their medical condition. This selective pattern has also been described in previous studies [1,3,7] and demonstrates that the changes observed are not the result of nonspecific cell proteolysis.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the soluble isoform of DPPIV showed a similar activity pattern, with statistically significant results when considering the gender of the patient with CT. Recently, Vlahović et al [1] demonstrated that DPPIV activity in serum is altered in patients with CT and TH, and normalizes after tonsillectomy. They also reported that the level of DPPIV in serum from individuals with CT was higher in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased CD26 expression has also been reported for other inflamed tissues, e.g. palatine tonsils [28] in humans and allergic-like airway inflammation in rats [18]. However, to our knowledge, this is the first report of enhanced CD26 expression in AD and CD lesions.…”
Section: Discussionsupporting
confidence: 50%
“…Para evaluar el efecto directo de la sitagliptina sobre su blanco farmacológico, se cuantificó la actividad de la enzima DPP-IV en el plasma de animales controles y tratados a través de la conversión de Gly-Pro p-nitroanilida a p-nitroanilina. La formación de p-nitroanilina se midió espectrofotométricamente (390 nm) a distintos tiempos 34 . La actividad del grupo tratado con sitagliptina se expresó en forma relativa a la actividad de los animales controles.…”
Section: Materials Y Métodosunclassified